A new troglobitic species of the spider genus Tengella Dahl (Araneae, Tengellidae) from Chiapas, Mexico - Candia-Ramírez, Daniela T.; Valdez-Mondragón, Alejandro (Zootaxa, 2014)
A new species of troglobitic spider of the genus Tengella Dahl is described from Mexico: Tengella kalebi new species, from a limestone cave in Chiapas, Mexico. The species is described on the basis of adult male and females. This is the fifth species described for the genus Tengella, the third species described from Mexico, the first species that has notable troglomorphic modifications, and the first ecribellate Tengella species.